Ahead of their time: From progressive rock to the progressive alliance. Issue 3 (December 2015) - Robinson, Emily
Abstract : Emily Robinson traces the parallel paths of 'progressiveness' in rock music and politics – in both cases, she argues, to be progressive was at first something optimistic and forward‐looking but in the end came to be derided as 'expertise at the expense of authenticity'.